Image quality evaluation of a small animal PET scanner (Brazilian Journal of Radiation Sciences (BJRS), 2020)
Performance testing of small animal PET scanners is very important to ensure the high performance required for this particular type of PET scanner. In this sense, National Electrical Manufactures Association (NEMA) published its NU 4/2008 standards, a consistent and standardized methodology for measuring scanner performance parameters for small animal PET imaging. Imaging capabilities of the scanner LabPET SOLO 4 were tested during two years according NEMA NU 4/2008 methodology. Results indicates that the equipment, despite a decade of use, presents performance appropriated and similar to performance of equipments reported in Literature.